Skeletal and Dental age assessment methods: A Review (Journal of Pharmaceutical Negative Results, 2023)
Identification and determination of age is imperative for diversity of reasons that include disputed birth records, premature delivery, legal issues etc. Assessment of growth and development of a child helps in orthodontic, tooth development, shedding analysis, surgical and orthopedic management in dentistry.Dental age is one of the few measures of physiologic development that is uniformly applicable from infancy to late adolescence.Several methods have been proposed for the assessment of a child’s dental age.